Teologi Pembebasan Dalam Pendidikan Islam Perspektif Asghar Ali Engineer - Dedeh Azizah (Oasis : Jurnal Ilmiah Kajian Islam, 2019)
According to the view of liberation theology, Islamic education must be able to produce people who take a role in the social system that promotes justice as citizens and citizens of the world in the view of religion (just, not oppressed) who are damaged by humans themselves. From the explanation, the author was interested in conducting a study "Liberation Theology in Islamic Education Perspective of Asghar Ali Engineer".The formulation of the research problem is: 1. What is the meaning of Liberation Theology? 2. What is the Asghar Ali Engineer's PerspectiveÂ  Liberation Theology? 3. How is the Liberation Theological Implication for Islamic Education Asghar Ali Engineer Perspective? This research was conducted with literature research. His research methods include data sources, data collection and data analysis. The results of the study concluded that the Liberation Theology according to Asghar Ali Engineer was interpreted as freedom that emphasizes the aspect of reason or construct of thinking in interpreting the book (holy text). For him, theology is a reflection of existing social conditions, and thus a theology is socially constructed. Asghar's method of thinking is normative and transcendental. Theological Implications of Liberation for Islamic Education include; Islamic Education is a practice of liberation, curriculum development is carried out in line with the development of non-curriculum factors, including the effects of economic, political, social, cultural, legal and other changes, including the academic factors of the kurikuluym, Asghar Ali Engineer views the Qur'an, as well as the text other texts, can be interpreted by various methods.MenurutÂ  pandangan teologi pembebasan, pendidikan Islam harus mampu menghasilkan manusia yang mengambil peran dalam sistem sosial yang mengedepankan keadilan sebagai warga negara dan warga dunia dalam pandangan agama (manusia yang adil, tidak tertindas) yang dirusak oleh manusia sendiri. Dari paparan tersebut penulis merasa tertarik untuk melakuakan penelitian â€œTeologi Pembebasan dalam Pendidikan Islam Perspektif Asghar Ali Engineerâ€. Rumusan masalah penelitian ini adalah : 1. Apa makna Teologi Pembebasan? 2. Bagaimana Teologi Pembebasan Persepektif Asghar Ali Engineer? 3. Bagaimana Implikasi Teologi Pembebasan Bagi Pendidikan Islam Persepektif Asghar Ali Engineer? Penelitian ini dilakukan dengan penelitian literatur (Library research). Metode penelitiannya mencakup sumber data, pengumpulan data, dan analisis data. Hasil penelitian disimpulkan bahwa Teologi Pembebasan menurut Asghar Ali Engineer adalah diartikan sebagai kebebasan yang menitik beratkan pada aspek akal atau konstruk berpikir dalam menafsirkan kitab (teks suci). Baginya, teologi adalah refleksi dari kondisi sosial yang ada, dan dengan demikian suatu teologi adalah dikonstruksi secara sosial. Metode pemikiran Asghar bersifat normatif, kontekstual dan transendental. Implikasi Teologi Pembebasan Bagi Pendidikan Islam diantaranya; Pendidikan Islam Merupakan Praktik Pembebasan, Pengembangan kurikulum dilakukan searah dengan perkembangan faktor Non-Kurikulum, antara lain akibat perubahan ekonomi, politik, sosial, budaya, hukum dan lain-lain, termasuk faktor akademik kurikuluymnya, Asghar Ali Engineer memandang Qurâ€™an, sebagaimana teks-teks lain, bisa diinterpretasikan dengan berbagai metode.